Communication—Analysis of Thick Co-Extruded Cathodes for Higher-Energy-and-Power Lithium-Ion Batteries. Issue 7 (29th April 2017) - Cobb, Corie L.; Solberg, Scott E.
Abstract : 3-dimensional (3D) electrode architectures have been explored as a means to decouple power and energy trade-offs in thick battery electrodes. Limited work has been published which systematically examines the impact of these architectures at the pouch cell level. This paper conducts an analysis on the potential capacity gains that can be realized with thick co-extruded electrodes in a pouch cell. Our findings show that despite lower active material composition for each cathode layer, the effective gain in thickness and active material loading enables pouch cell capacity gains greater than 10% with a Lithium Nickel Manganese Cobalt Oxide (NMC) materials system.